Original copies: seriality, similarity and the simulacrum in the Early Bronze Age - Sørensen, Tim Flohr (Danish Journal of Archaeology, 2012)
This article explores inter-artefactual relations in the Nordic Bronze Age. Notions of copying and imitation have been dominant in the description of a number of bronze and flint artefacts from period I of the Nordic Bronze Age (ca. 1700–1500 BC). It has been argued that local bronze manufacturers copied imported foreign artefacts, and that lithic producers tried to imitate bronze artefacts in flint. This article argues that these archaeological attitudes to resemblance in the material repertoire are a product of typological analyses, but that it is possible to reclaim the cultural reality of similarity by looking at artefactual similarity as the results of prototyping and as a production of simulacra. In this light, the concept of copying turns out to be more than simply a matter of trying to imitate an exotic or prestigious original, and it fundamentally raises the question how different a copy can be from its model and still be a copy.